PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN TATA BOGA BERBASIS HOSPITALITY UNTUK MENDUKUNG PARIWISATA BERKELANJUTAN DI KELURAHAN TANJUNG BUNTUNG, KECAMATAN BENGKONG - Hendra Syaiful; Wahyudi Ilham; Agung Edy Wibowo; Yudha Wardani; Hari Sandi Atmaja (Bajang Institute, 2026)
Charcoal Batik is a unique product of the Sawahlunto creative industry, possessing a unique local culture based on its coal mining history. However, Batik Arang MS Sawahlunto's artisan partners still face serious challenges in terms of market visibility, weak brand identity, and limited adoption of digital marketing technology. This Community Service (PKM) activity aims to strengthen branding strategies and expand online market reach to boost partners' competitive advantage. The community service implementation method uses a participatory approach that includes field observations, interactive workshops, and intensive coaching in the creation of digital marketing assets. The results of this activity demonstrate a significant increase in partner capacity, marked by the development of a professional brand visual identity, ownership of business social media accounts (Instagram and TikTok), and understanding of e-commerce management. Through this sustainability program, Batik Arang MS Sawahlunto now has digital independence to reach regional and national markets